Perbandingan Pengetahuan dan Sikap tentang PCOS pada Mahasiswi Kesehatan dan Non Kesehatan - Wilda Qotrunnada Salsabila; Adyani, Kartika; Realita, Friska (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2024)
Background: Polycystic Ovary Syndrome (PCOS) is a common reproductive problem in women of childbearing age, with a global prevalence of 3.4% and 5–10% in Indonesia. PCOS can cause infertility, as well as metabolic and psychological disorders. The main symptom is irregular menstruation, which is often associated with poor dietary habits such as junk food consumption, especially in female students. Lack of knowledge about PCOS among adolescents and female students triggers inappropriate attitudes towards this condition. Method: This research is a quantitative research using a comparative study design with a cross-sectional design. The sample of 94 health students and 94 non-health students was obtained through proportionate sampling with a stratified random method. Data collection used a questionnaire and was analyzed using the Independent Sample T-Test and Maan Whitne. Result: The results of the study showed that the average and median values ​​of knowledge and attitudes of health students were higher than non-health students, the difference between the two variables was (p<0.05). These results indicate that there are differences in knowledge and attitudes between health and non-health students. Health students have better knowledge and attitudes. Implications: For health and non-health students, it is expected to improve reproductive health literacy, participate in health education or seminars, especially regarding PCOS considering that this syndrome can affect women's quality of life and long-term health.